Soulèvement populaire au pays de Chávez - Julien Rebotier (EchoGéo)
From February 2014 on, isolated and violent riots are striking Venezuela. Its historical, socio-political and economical contexts allow making connexions with current Latin-American challenges. Stemming from a socio-historical and geographical perspective, a contextual and prospective analysis of such violence brings a better understanding of the events instead of merely judging a government. The analysis also brings Venezuelan riots into a continental crossroads: between the emerging of strong social queries (services, democracy, consumption) and the weakness of States that are only recently getting stronger from the regional left turn of the 2000. In front of the reiterated threat of breaking both legal and constitutional orders, the budding (re)politicization of Latin-American societies might improve a culture of politics, strengthen a democratic order, and consolidate still weak national sovereignties in the region.